Reforming modernity : ethics and the new human in the philosophy of Abdurrahman Taha - Hallaq, Wael B., 1955- (Columbia University Press, 2019)
"Wael Hallaq explores the history, development, and contemporary trends in Muslim political thought using the work of Morocco-based philosopher Taha Abdurrahman. A sweeping intellectual history and philosophical examination, this book examines the trajectory of how we understand the central questions plaguing modernity in both the West and Muslim lands"--